Association of Consumption Patterns and Eating Habits with Household Nutritional Status in Mountainous and Coastal Areas of Banyuwangi - Dea Amanda Caressa; Intan Gumilang Pratiwi (Indonesian Health Issue, 2026)
Family nutritional status remains a major public health concern, particularly in regions with diverse geographical characteristics that influence food availability and dietary behavior. Variations in dietary patterns and eating habits between mountainous and coastal areas may contribute to differences in nutritional outcomes at the household level. This study aimed to examine the association between dietary patterns and eating habits with family nutritional status and to identify regional differences in these associations in Banyuwangi Regency, Indonesia. A quantitative cross-sectional study was conducted from August to September 2025 involving 110 families selected using multistage sampling. Data were collected through a locally adapted Food Frequency Questionnaire (FFQ), structured eating habit questionnaires, and anthropometric measurements based on WHO standards. Statistical analyses included descriptive statistics, Chi-Square tests, and multivariate logistic regression. The results indicated that a substantial proportion of families exhibited inadequate dietary patterns and unhealthy eating habits, alongside significant differences in nutritional status between mountainous and coastal regions. Both dietary patterns and eating habits were significantly associated with family nutritional status after adjusting for potential confounders, with inadequate dietary patterns emerging as the strongest determinant. Stratified analysis revealed regional-specific determinants, where dietary patterns were more influential in mountainous areas, while eating habits played a greater role in coastal areas. In conclusion, improving family nutritional status requires region-specific nutrition interventions that address local food systems and promote balanced dietary practices through targeted nutrition education.